A model to determine at‐home restrictions for cats after treatment of hyperthyroidism with radioiodine. (1st August 2022) - Peak, K.; Alonzi, C.; Gower, L.; Walker, D.; Johnson, B.
Abstract : Objectives: Felinehyperthyroidism is the most common endocrine disease of older cats and radioiodine is considered to be the gold standard treatment. Isolation periods following treatment vary depending on both individual treatment facilities and the relevant legislation of the country; therefore, there is no recognised standardised protocol defining the length of isolation. This work describes how our institution validated that its owner restrictions met dose constraints by using a model of iodine retention to calculate the required duration and nature of owner restrictions. Materials and Methods: The retained radioactivity of cats at the point of discharge was used to simulate the radiation dose to owners in the 90 days following release. The model created was used to calculate the minimum duration of isolation for a range of administered activities and owner restrictions. Results: Using the model, it was found that when injected with the maximum dose used, 222 MBq radioiodine, it was possible to release cats after 14 days of isolation and keep owner doses below 0.30 mSv (whole‐body effective dose constraint for a single radiation source) with some restrictions. It was possible to release after 23 days with no restrictions. Clinical Significance: The present study provides clinicians with a consistent and verified method in which they can calculate the isolation periods for radioiodine‐treated cats.